2020
DOI: 10.1007/s11886-020-01292-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Complications in Patients with COVID-19: Consequences of Viral Toxicities and Host Immune Response

Abstract: Purpose of Review Coronavirus disease of 2019 (COVID-19) is a cause of significant morbidity and mortality worldwide. While cardiac injury has been demonstrated in critically ill COVID-19 patients, the mechanism of injury remains unclear. Here, we review our current knowledge of the biology of SARS-CoV-2 and the potential mechanisms of myocardial injury due to viral toxicities and host immune responses. Recent Findings A number of studies have reported an epidemiological association between history of cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
186
1
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(205 citation statements)
references
References 82 publications
3
186
1
15
Order By: Relevance
“…This entry mechanism is con rmed by the fact that TMPRSS2 inhibition or TMPRSS2-KO mice show both decreased, though not abolished, S protein priming, and reduced viral entry, spread, as well as, in ammatory chemokine and cytokine release [19]. Second, there may be an imbalance between Th1 and Th2 responses in COVID-19 patients, and the cytokine storm triggered by this imbalance may be another mechanism of myocardial injury [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This entry mechanism is con rmed by the fact that TMPRSS2 inhibition or TMPRSS2-KO mice show both decreased, though not abolished, S protein priming, and reduced viral entry, spread, as well as, in ammatory chemokine and cytokine release [19]. Second, there may be an imbalance between Th1 and Th2 responses in COVID-19 patients, and the cytokine storm triggered by this imbalance may be another mechanism of myocardial injury [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It is an enveloped virus with single stranded positive sense Ribo Nucleic Acid (RNA) as a genetic material. COVID-19 infection predominantly causes respiratory illness with asymptomatic or mildly symptomatic fever, cough, fatigue and diarrhea and severe acute respiratory distress syndrome (ARDS) along with fatal multi organ collapse in certain cases [14]. COVID-19 incorporates spike protein which first binds itself to the Angiotensin Converting Enzyme 2 (ACE 2) receptor on the host cell surface.…”
Section: Fundamental Mechanism For Covid-19 Infectionmentioning
confidence: 99%
“…Tachycardia may result from high cytokine levels, which activate cardiac pacemaker cells in the state of infection, or from direct myocardial invasion, as multiple studies have suggested (35,36). Since tachycardia is one of the initial manifestations of acute heart failure, patients presenting tachycardia may need evaluation for acute cardiac injury, a fatal complication of COVID-19.…”
Section: Symptomsmentioning
confidence: 99%